(untitled) (Research, Society and Development, 2021)
Music causes different physiological responses, some of which are changes in blood pressure, heart rate and respiratory rate. In the researched literature, few studies were found that assess the effects of music on cardiac autonomic modulation, especially in active cardiac patients. Thus, the aim of the present study was to evaluate the autonomic modulation of heart rate under the effect of musical stimulation, through the analysis of heart rate variability by linear and non-linear methods. Methodology: Eleven active heart disease patients participated in the study. The volunteers remained, before the beginning of the test, at rest for five minutes and 30 seconds and were exposed to four songs with different rhythms, at random, for five minutes and 30 seconds each; with an interval of 15 seconds between them. The linear and non-linear, statistical and geometric indices in the time domain and the indices in the frequency domain were analyzed. For data analysis, the Friedman test was performed, with post-test Bonferroni, with a significance level of 5%. Results: Mean values of repetitive heart beats were found significantly higher (p<0.05) during the song "Send my love" when compared to rest. It was observed that no statistically significant values were found in the different powers pectra, in the BF ratio/AF and in non-linear indices, when comparing different musical exposures and at rest. Conclusion: The heart rate variability indices were not altered by musical exposure in this studied population.